Life in transition: nostalgia as change-related emotion - Sarcinella, Eleonora Diletta; Liedgren, Johan; Chirico, Alice (Frontiers in Virtual Reality, 2025)
Nostalgia is a complex emotion that connects the present with both the remembered past and the imagined future. While traditionally studied in its past-oriented form, future-oriented variants, such as anticipatory and anticipated nostalgia, remain underexplored, partly due to methodological challenges. Although these forms also engage prospective cognitive processes, like episodic future thinking and mental simulation, they have usually been addressed through conventional, memory-based paradigms. This perspective proposed novel methodological design guidelines for eliciting nostalgia across its full temporal spectrum (past and future oriented variants) by combining Virtual Reality (VR) with a specific class of content: liminal spaces, contexts marked by transition and ambiguity. VR offers immersive and controllable environments, while liminal settings symbolically reflect change, a core feature of nostalgic experience. Specifically, we offered design guidelines for constructing liminal spaces aimed at eliciting both past- and future-oriented nostalgia, through the manipulation of two key variables: familiarity and ambiguity. This approach seeks to enhance experimental control and ecological validity, addressing current limitations in nostalgia research. Finally, it offered potential clinical applications, especially in contexts where reconnecting with meaning and future self-continuity is essential, such as during life transitions or emotional distress.